2014
DOI: 10.3390/ijms15034221
|View full text |Cite
|
Sign up to set email alerts
|

Structure of N-Terminal Sequence Asp-Ala-Glu-Phe-Arg-His-Asp-Ser of Aβ-Peptide with Phospholipase A2 from Venom of Andaman Cobra Sub-Species Naja naja sagittifera at 2.0 Å Resolution

Abstract: Alzheimer’s disease (AD) is one of the most significant social and health burdens of the present century. Plaques formed by extracellular deposits of amyloid β (Aβ) are the prime player of AD’s neuropathology. Studies have implicated the varied role of phospholipase A2 (PLA2) in brain where it contributes to neuronal growth and inflammatory response. Overall contour and chemical nature of the substrate-binding channel in the low molecular weight PLA2s are similar. This study involves the reductionist fragment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The article entitled with “Structure of N -Terminal Sequence Asp-Ala-Glu-Phe-Arg-His-Asp-Ser of Aβ-Peptide with Phospholipase A 2 from Venom of Andaman Cobra Sub-Species Naja naja sagittifera at 2.0 Å Resolution” authored by Professor Dr. Zeenat Mirza, and coauthors reported the structure from Alzheimer’s Aβ-peptide in complex with phospholipase A 2 , which was determined by X-ray crystallography at 2.0 Å resolution [ 9 ]. Their findings suggest the possibility of interactions between N -terminus residues (DAEFRHDS) and phospholipase A 2 .…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…The article entitled with “Structure of N -Terminal Sequence Asp-Ala-Glu-Phe-Arg-His-Asp-Ser of Aβ-Peptide with Phospholipase A 2 from Venom of Andaman Cobra Sub-Species Naja naja sagittifera at 2.0 Å Resolution” authored by Professor Dr. Zeenat Mirza, and coauthors reported the structure from Alzheimer’s Aβ-peptide in complex with phospholipase A 2 , which was determined by X-ray crystallography at 2.0 Å resolution [ 9 ]. Their findings suggest the possibility of interactions between N -terminus residues (DAEFRHDS) and phospholipase A 2 .…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…Some results have been indicated that the Aβ forms an ion channel and is responsible for an elevation of cytoplasmic Ca 2+ . The Aβ channel hypothesis proposes that the hydrophilic N‐terminus third (residues 1‐14, S1) of amyloid peptide composes the lining of the Aβ channel's pore, which encompasses the His13‐His14 diad around the axis . The channel is electronegative, characterized by its selective affinity with cations including Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The article entitled with "Structure of N-Terminal Sequence Asp-Ala-Glu-Phe-Arg-His-Asp-Ser of Aβ-Peptide with Phospholipase A2 from Venom of Andaman Cobra Sub-Species Naja naja sagittifera at 2.0 Å Resolution" authored by Professor Dr. Zeenat Mirza, and coauthors reported the structure from Alzheimer's Aβ-peptide in complex with phospholipase A2, which was determined by X-ray crystallography at 2.0 Å resolution [9]. Their findings suggest the possibility of interactions between N-terminus residues (DAEFRHDS) and phospholipase A2.…”
Section: Structure-based Drug Designmentioning
confidence: 99%